El Derecho de Competencia Económica en la Constitución del Ecuador - Marcelo Marín Sevilla (Universidad Hemisferios, 2010)
This work allows us to establish the Economic Constitution and the Competition Law (C.L) in the Constitution. Additionally, the paper analyzes whether the rules outlined in the C. L. and in doctrine are consistent and appropriate with the Constitution of Ecuador. The Competition and Antitrust Laws has rules for investigating and punishing the cartels, the abuses of power market (dominant position), the rules for merger control, the behaviors of Abuse of economic dependence, and unfair competition behaviors. Always the Antitrust Authority will analyze these behaviors in terms of welfare of both: the consumer and the market.